Building Approvals as a Leading Indicator of Property Sector Investment (International Journal of Banking and Finance, 2012)
Overall, building approvals for new houses (BANHs) are viewed by most economic analysts/commentators as a leading indicator of property investment due to the importance of this sector to the whole economy and employment. This study seeks shed some additional light on modelling this seasonal behaviour of BANHs by: (i) establishing the presence of seasonality in Victorian BANHs; (ii) ascertaining it as to whether is deterministic or stochastic; (iii) estimating out-of-sample forecasting capabilities of the modelling specification; and (iv) speculating on possible interpretation of results. The study utilises a structural time series model of Harvey. Factors corresponding to June, April, December and November are found to be significant at five per cent level. The observed seasonality could be attributed to both the summer holidays and the end of financial year seasonal effects. Irrespective of partially incomplete nature of this research, the findings should be appealing to, among others, researchers, all levels of Government, construction industry and banking industry.